HUBUNGAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI TEKS NARASI DI SDN 10 LANGSA - Fitria Annisa; Alpidsyah Putra; Juliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low learning outcomes are caused by obstacles when students understand the material presented by the teacher, especially in the Indonesian Language subject. To avoid comparisons in learning achievement, teachers should provide instruction with diverse learning styles for all students in the class. Therefore, it is important for the author to determine "How is Differentiated Learning Related to Fourth Grade Student Learning Outcomes in Narrative Text Material at SDN 10 Langsa?" This study aims to determine the relationship between Differentiated Learning and Fourth Grade Student Learning Outcomes in Narrative Text Material at SDN 10 Langsa. The research method used was correlation research. The sampling technique used was probability sampling with simple random sampling, so the sample was 24 fourth grade students in grade 4b. Data obtained in this study came from student response questionnaires and learning outcome scores. The results of the study indicate that there is a relationship between differentiated learning and student learning outcomes, with a moderate strength and a positive correlation. Therefore, it can be concluded that the better the implementation of differentiated learning, the better the student learning outcomes.